2006
DOI: 10.1007/s10479-006-0121-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of depreciation allowances on the timing of investment and government tax revenue

Abstract: We develop a model of the behavior of a potential investor (under uncertainty and in a fiscal environment) who wishes to invest into a project in the real sector of an economy and faces a timing problem. We find an optimal solution within this model and examine the dependence of the tax revenue from the newly created firm on the depreciation policy. It is shown that there exists a domain in the space of the parameters of the investment project where both the tax revenue and the incentives can be increased by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
0
12
0
2
Order By: Relevance
“…Along with the use of accelerated depreciation, small businesses can write off a further depreciation of up to 50% of the original cost of fixed assets with a service life of more than three years (Arkin & Slastnikov, 2007).…”
Section: Experience Of Developed Countriesmentioning
confidence: 99%
See 3 more Smart Citations
“…Along with the use of accelerated depreciation, small businesses can write off a further depreciation of up to 50% of the original cost of fixed assets with a service life of more than three years (Arkin & Slastnikov, 2007).…”
Section: Experience Of Developed Countriesmentioning
confidence: 99%
“…Wakeman (1980) has shown that if the tax rate is flat and if taxable income is non-negative in all periods for all available depreciation methods, the accelerated depreciation method is most preferable for tax purposes. With reference to the Russian system of profit taxation, the investment waiting model, which is a development of the McDonald-Siegel model, was proposed by Arkin and Slastnikov (2007). The extension of this model by the introduction of a lag period between the moment of investment and production was studied by Arkin and Slastnikov (2007).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, since the depreciation method affects the timing of tax payments, it affects the net present value of the firm's after-tax revenues. Existing literature shows that tax depreciation can significantly affect the value of the firm and its investment behavior (see, e.g., Arkin and Slastnikov 2007;De Waegenaere et al 2003;Sansing 1998;Wielhouwer et al 2000).…”
Section: Introductionmentioning
confidence: 99%